Ethnopedagogy as an approach to primary education - Gunardi, Ari; Muhyidin, Asep; Leksono, Suroso Mukti; Jamaludin, Ujang (Institute of Computer Science (IOCS), 2024)
Ethnopedagogy is one of the approaches implemented in learning. An approach that prioritizes the cultural value of local wisdom in learning and is an approach that recognizes cultural diversity and local knowledge as important resources in the learning process. The aim of this research is to examine and understand how values, norms and traditions in the ethnopedagogical approach are based on concepts, learning and strengthening ethnopedagogical values. This research uses a type of literature study. The results of the literature study showed that the ethnopedagogical concept is a holistic, culture-based learning practice. The implementation of ethnopedagogy in basic education can be integrated into classroom subject learning such as science, social studies, as well as languages and arts. However, it cannot be denied that other materials can be implemented in basic education. There are several strengthening local wisdom values that can be implemented with an ethnopedagogical approach such as a multicultural approach, teacher training, and integration in the curriculum. In the future, the concept of an ethnopedagogical approach in basic education can be studied in more detail regarding its implementation and obstacles. Practical implications of this research include developing pedagogy that is more responsive to the needs of students from diverse cultural backgrounds, as well as strengthening the relationship between formal education and local knowledge in building more inclusive and sustainable societies.